Rare severe hypofibrinogenemia induced by tissue plasminogen activator in stroke patients: Case report. Issue 9 (5th March 2021) - Huang, Xuming; Cao, Liming
Abstract: Rationale: Severe hypofibrinogenemia after intravenous thrombolysis (IVT) with recombinant tissue plasminogen activator (rt-PA) is rare and easily overlooked, but hypofibrinogenemia increases the risk of major bleeding. However, it is unclear when hypofibrinogenemia reaches the peak and when hypofibrinogenemia is resolved. Patient concerns: Case 1 was of a 66-year-old man who was hospitalized due to sudden onset of vague speech and right hemiplegia for 4 hours. Case 2 was of an 84-year-old woman who was hospitalized for sudden onset of left hemiplegia and vague speech for 4 hours. In case 1, fibrinogen levels decreased from normal values to <0.25 g/L within 4.5 hours after commencing IVT and returned to normal at 35 hours later. In case 2, fibrinogen levels decreased from 1.1 to <0.25 g/L within 2 hours after commencing IVT and normalized 36.5 hours later. Diagnoses: Both patients were diagnosed with rt-PA-related hypofibrinogenemia. Interventions: No antiplatelet or symptomatic treatment was administered during the period of hypofibrinogenemia. Outcomes: Fibrinogen levels gradually recovered. In case 1, the patient did not experience cerebral hemorrhage during hypofibrinogenemia. His symptoms improved significantly within 1 week. In case 2, repeat computed tomography revealed minor cerebral hemorrhage, but no deterioration in her condition was noted until she was discharged. Lessons: Rapid, severe, and prolonged hypofibrinogenemia may occur after IVT with rt-PA, which may increase the risk of massive hemorrhage and affect the related therapy. Prompt diagnosis of hypofibrinogenemia is important for preventing complications. We recommend checking the fibrinogen levels routinely after IVT. Fibrinogen replacement therapy and platelet transfusion are the main management routes for rt-PA-related symptomatic intracranial hemorrhage.